Nutrient Control of Yeast Gametogenesis Is Mediated by TORC1, PKA and Energy Availability. - Hilla Weidberg; Fabien Moretto; Gianpiero Spedale; Angelika Amon; Folkert J van Werven (PLoS Genetics)
Cell fate choices are tightly controlled by the interplay between intrinsic and extrinsic signals, and gene regulatory networks. In Saccharomyces cerevisiae, the decision to enter into gametogenesis or sporulation is dictated by mating type and nutrient availability. These signals regulate the expression of the master regulator of gametogenesis, IME1. Here we describe how nutrients control IME1 expression. We find that protein kinase A (PKA) and target of rapamycin complex I (TORC1) signalling mediate nutrient regulation of IME1 expression. Inhibiting both pathways is sufficient to induce IME1 expression and complete sporulation in nutrient-rich conditions. Our ability to induce sporulation under nutrient rich conditions allowed us to show that respiration and fermentation are interchangeable energy sources for IME1 transcription. Furthermore, we find that TORC1 can both promote and inhibit gametogenesis. Down-regulation of TORC1 is required to activate IME1. However, complete inactivation of TORC1 inhibits IME1 induction, indicating that an intermediate level of TORC1 signalling is required for entry into sporulation. Finally, we show that the transcriptional repressor Tup1 binds and represses the IME1 promoter when nutrients are ample, but is released from the IME1 promoter when both PKA and TORC1 are inhibited. Collectively our data demonstrate that nutrient control of entry into sporulation is mediated by a combination of energy availability, TORC1 and PKA activities that converge on the IME1 promoter.